KEANEKARAGAMAN JENIS GASTROPODA DI KAWASAN HUTAN MANGROVE EQUATOR PARK DESA JERUJU BESAR KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Ranggara, Dealit; Darwati, Herlina; Riyono, Joko Nugroho (Universitas Tanjungpura, 2024)
The mangrove forest of Jeruju Besar Village, Sungai Kakap District, Kubu Raya Regency, is still maintained and is still in natural condition. The mangrove forest vegetation in Equator Park is dominated by nipa palm, due to the influence of abrasion and tides in the mangrove forest, so that the vegetation is not diverse. This ecosystem has various types of flora and fauna, one of which is gastropods. This study aims to examine the main purpose diversity of gastropods in the mangrove forest area of Equator Park Jeruju Besar, Jeruju Besar Village, Sungai Kakap District, Kubu Raya Regency. Data collection in the field is carried out in 3 lanes. Each lane consists of 10 plots measuring 1x1 meter. The distance between each plot is 30 meters long and the distance between lanes is 30 meters. The laying of lane 1 and the first plot was purposive based on the consideration of the presence of vegetation in the mangrove forest and the presence of gastropods. The next plot is carried out systematic. The gastropods found were 219 individuals. There are 5 different families of 8 species, namely Cassidula aurisfelis, Ellobium aurisjudae, Littoraria angulifera, Littoraria undulata, Malea pomum, Nerita pollita, Neritina violacea, and Polinices albumen. The diversity of H